2019
DOI: 10.30872/jim.v14i1.1252
|View full text |Cite
|
Sign up to set email alerts
|

Peramalan Angka Inflasi Kota Samarinda Menggunakan Metode Double Exponential Smoothing (Studi Kasus : Badan Pusat Statistik Kota Samarinda)

Abstract: Inflasi merupakan suatu kondisi kenaikan harga-harga umum secara terus menerus yang berhubungan dengan mekanisme pasar dinilai berdsarkan indeks harga konsumen (IHK)  oleh Badan Pusat Statistik. Masalah yang dihadapi oleh Badan Pusat Statistik yaitu belum terdapat sistem yang dapat melakukan peramalan angka inflasi untuk 1 tahun mendatang yang dijadikan acuan untuk mengambil tindakan pencegahan. Maka dari itu diperlukan sistem yang dapat melakukan peramalan angka inflasi secara otomatis. Metode yang digunakan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 0 publications
0
7
0
9
Order By: Relevance
“…In this DES method, the calculation is done twice to calculate the level and the trend. Still using the same sales data, the following is the DES calculation for the level using equation (2). In contrast, the movement uses equation (3).…”
Section: Double Exponential Smoothing (Des)mentioning
confidence: 99%
See 3 more Smart Citations
“…In this DES method, the calculation is done twice to calculate the level and the trend. Still using the same sales data, the following is the DES calculation for the level using equation (2). In contrast, the movement uses equation (3).…”
Section: Double Exponential Smoothing (Des)mentioning
confidence: 99%
“…Forecasting the inflation rate using the double exponential smoothing method and looking for the slightest error value with MSE and alpha values of 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9. This study was able to predict the 2018 Inflation Figure Forecast in the city of Samarinda based on inflation data for 2013-2017 with the smallest error value at an alpha value of 0.3, which was measured using the mean square error [2].Predicting the number of train passengers in 2018 using the Single Exponential Smoothing and Double Exponential Smoothing methods than using checking the error values of SSE, MSE, and MAPE at alpha 1 and 0.5 values using train passenger training data from January 2006 -December 2015 and January 2016 -October 2017 as test data. The SSE accuracy value of 157444122 is found in the Double Exponential Smoothing method, and it can be concluded that train passengers in Indonesia will increase every month in 2018 [3].…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Peramalan inflasi dapat dilakukan dengan berbagai metode di antaranya adalah extreme learning machine [6], support vector regression [7], exponential smoothing [8], fuzzy time series [9], multiple regression [10], ensembel [11], dan neural network [10], [12], [13]. Metode neural network sendiri adalah salah satu metode kecerdasan buatan yang banyak digunakan dalam peramalan termasuk dalam peramalan inflasi di dunia [14][15] dan beberapa penelitian yang pernah dilakukan di Indonesia [10], [12], [13].…”
unclassified